Clinical and genetic study of a Chinese family affected by both amyotrophic lateral sclerosis and autosomal dominant polycystic kidney disease - Li, Shirong; Lin, Junyu; Li, Chunyu; Chen, Yongping; Cao, Bei; Yang, Tianmi; Wei, Qianqian; Zhao, Bi; Chen, Xueping; Shang, Huifang (Frontiers in Neurology, 2022)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder characterized by loss of the upper and lower motor neurons from the motor cortex, brainstem, and spinal cord. Most ALS cases are sporadic, with 5–10% having a positive family history. Autosomal dominant polycystic kidney disease (ADPKD) is a heritable renal disease that eventually results in end-stage kidney disease. PKD1 is the most prevalent causative gene for ADPKD, accounting for ~85% of cases. Both diseases are currently considered untreatable. In this study, we report a large family that includes 10 patients with ALS phenotype, 3 asymptomatic SOD1-H47R carriers, and 6 with the ADPKD phenotype. Using whole exome sequencing, we found a novel likely pathogenic variant (p.R2787P) in PKD1 among patients with ADPKD, and a pathogenic variant (p.H47R) in SOD1 among patients with ALS. This study highlights the possibility that two different autosomal dominantly inherited diseases can co-exist independently within the same family. Phenotype—genotype correlations among these patients are also described. This research contributes novel phenotype and genotype characteristics of ALS with SOD1 mutations and ADPKD with PKD1 mutations.